Letter : Spain - political assassinations - Gallie, C. N.
013-0050-001 RAILWAY CLERKS' ASSOCIATION OF GREAT BRITAIN AND IRELAND TELEGRAPHIC ADDRESS "FORESHADOW WELWYN GARDEN CITY" TELEPHONE WELWYN GARDEN 3337/8 GENERAL SECRETARY C. N. GALLIE Representing the Clerical, Administrative, Professional, Technical and Supervisory Employees in all Departments of the Railways and Allied Undertakings, and London Transport HEAD OFFICE MIDLAND BANK CHAMBERS, HOWARDSGATE, WELWYN GARDEN CITY Ref.P. 24th December, 1940. Mr. H. V. Tewson, Assistant Secretary, Trades union Congress, Transport House, Smith Square, London, S.W.1. Dear Mr. Tewson, SPAIN - POLITICAL ASSASSINATIONS I am obliged for your letter of 20th instant, Reference HVT/AC/DT/321, and it was thought desirable, although I was aware of what transpired at our last General Council meeting, that you should know the feeling of our Executive Committee in this matter. I agree that in the light of the report submitted by the Chairman and yourself it is only necessary for you to note the resolution. Yours faithfully, C.N. Gallie 292/946/13/50